PERSEPSI SISWA ATAS PENGARUH KETERAMPILAN MENGAJAR GURU DAN PENGELOLAAN KELAS TERHADAP PRESTASI BELAJAR SISWA - Partono, - (Dinamika Pendidikan, 2009)
The statements of the problem are (1) How is the studentÃ¢â¬â¢s perception due toÃÂ  teacherÃ¢â¬â¢s ability in teaching on 2nd in class administration office education program at Palebon Vocational School Semarang (2) How is the studentÃ¢â¬â¢s perception due to the class management toward studentsÃ¢â¬â¢ learning achievementÃÂ  on 2nd class in Vocational School Palebon Semarang?, (3) How is the studentÃ¢â¬â¢s perception due to teacherÃ¢â¬â¢s ability inÃÂ  teaching and class management toward studentsÃ¢â¬â¢ learning achievementÃÂ  on 2nd class inÃÂ  administration office education program at Palebon Vocational School Semarang, the objectives of this research are : (1) to analyze the studentÃ¢â¬â¢s perception due to the influence of teacherÃ¢â¬â¢s skill in teachingÃÂ  toward learning achievement on 2nd class at Vocational School Palebon Semarang. (2) to analyze the studentÃ¢â¬â¢s perception due to the influence class management toward learning achievement on 2nd class in Vocational School Palebon Semarang. (3) to analyze the studentÃ¢â¬â¢s perception due to the ability of teaching and class management toward learning achievement on 2nd class administration office education program in Palebon Vocational School Semarang. The population of this research was students of 2nd class in office administration program with the number was 60 students. Result of study showed that the ability of learning and class management was in a good category. This can be seen from the percentage of 61,7%.ÃÂ  Teaching and class management was 58,3%, it was a very good category. Thus, The research gave a significant contribution towards learning achievement with multiple regression analysis: from the a regression analysis equality Y =ÃÂ  4,937 + 0,020 X1 +ÃÂ  0,024X2. The percentage effect of teaching ability towards learning achievement according determination coeficient value is 32,4%. Based on the result above, it can be concluded that studentÃ¢â¬â¢s perception by the ability of learningÃÂ  was in a very good category for 61,7 %. Besides that, the influence of teaching ability and class management was 10,3%. Thus, it is suggested that teachers should improve their teaching method, and can apply the teaching equipment and media. Key words: management class, teacherÃ¢â¬â¢s ability in teaching